Characteristics of Motorcycle Ownership and Use of University Students in Malaysian and Indonesian Cities - Leksmono Suryo Putranto; Joewono Prasetijo; N.P.S.E. Setyarini (Institute of Research and Community Outreach - Petra Christian University, 2015)
Motorcycle ownership and use increased rapidly in Indonesian cities in recent years. People could not cope with severe congestion due to unsatisfactory public transport and uncontrolled land use delopment. This led to motorcycle use for almost any trip. However, in Malaysia motorcycles were mainly used for local short distance travel. In this paper the characteristics of motorcycle ownership and use of university students in Malaysian and Indonesian cities were discussed. A total of 398 university students in eight cities were asked to fill the questionnaires. They consist of general questions regarding their socio-economic back-ground and travel habit along with 25 perceptional questions regarding affordability/ attractiveness of owning motorcycle and practicability/safety of motorcycle use. A variance based structural equation modelling called partial least square-path modelling (PLS-PM) was used for analysis. The results show that indicators explaining affordability and acceptability were exactly the same in Penang and combination of seven cities in Indonesia.